Survival by colon cancer stage and screening interval in Lynch syndrome: a prospective Lynch syndrome database report - Dominguez-Valentin, Mev; Kloor, Matthias; Knebel Doeberitz, Magnus von; Ahadova, Aysel (Hereditary cancer in clinical practice, 2019)
We previously reported that in pathogenic mismatch repair (path_MMR) variant carriers, the incidence of colorectal cancer (CRC) was not reduced when colonoscopy was undertaken more frequently than once every 3 years, and that CRC stage and interval since last colonoscopy were not correlated.
Gesehen am 13.11.2019